2017
DOI: 10.1016/j.celrep.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Elevation of a Klotho Fragment Enhances Brain Function and Resilience in Young, Aging, and α-Synuclein Transgenic Mice

Abstract: SUMMARYCognitive dysfunction and decreased mobility from aging and neurodegenerative conditions, such as Parkinson and Alzheimer diseases, are major biomedical challenges in need of more effective therapies. Increasing brain resilience may represent a new treatment strategy. Klotho, a longevity factor, enhances cognition when genetically and broadly overexpressed in its full, wild-type form over the mouse lifespan. Whether acute klotho treatment can rapidly enhance cognitive and motor functions or induce resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 71 publications
6
101
0
7
Order By: Relevance
“…These results are in agreement with former studies that demonstrated that exercise increases αKL levels (Matsubara et al, 2014, Santos-Dias et al, 2017 and cognitive improvement induced by αKL in animal studies (Dubal et al, 2014(Dubal et al, , 2015. As indicated by other animal studies (Leon et al, 2017), despite impermeability to the blood brain barrier, the administration of αKL protein fragment in the periphery can increase cognitive functions with neural resilience. These animal studies raise the possibility that the correlation of αKL changes and HC VOL changes could be due to indirect effects of αKL on neuroplasticity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with former studies that demonstrated that exercise increases αKL levels (Matsubara et al, 2014, Santos-Dias et al, 2017 and cognitive improvement induced by αKL in animal studies (Dubal et al, 2014(Dubal et al, , 2015. As indicated by other animal studies (Leon et al, 2017), despite impermeability to the blood brain barrier, the administration of αKL protein fragment in the periphery can increase cognitive functions with neural resilience. These animal studies raise the possibility that the correlation of αKL changes and HC VOL changes could be due to indirect effects of αKL on neuroplasticity.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of Klotho in mice causes cognitive impairment, whereas increasing Klotho improves hippocampal-dependent memory (Dubal et al, 2014(Dubal et al, , 2015. Since elevating Klotho serum levels in mice enhances cognition (Dubal et al, 2014(Dubal et al, , 2015Leon et al, 2017), strategies that increase Klotho activity or simulate its function may therefore improve cognition at different life stages and, possibly, even under pathological circumstances. Recent evidence suggests that Klotho is a regulator of postnatal neurogenesis, affecting neural stem cell proliferation and maturation sufficient to impact hippocampal-dependent spatial memory function (Laszczyk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After acclimation for 1 wk, weight-matched mice were randomized into 4 groups (n = 8/group) and treated s.c. with 1.5 mg/(kg/d) Tac (Prograft; Astellas Pharma, Tokyo, Japan) or 10 ml/(kg/d) vehicle (Vh; olive oil; MilliporeSigma, Billerica, MA, USA), with or without recombinant mouse Klotho (rKlotho; 10 mg/kg), once every 2 d by intraperitoneal injection for 4 wk. rKlotho protein, which contains the entire extracellular region (Ala35-Lys982), without the transmembrane domain and intracellular domain, was purchased from R&D Systems (Minneapolis, MN, USA), and its biologic activity has been extensively characterized by the manufacturer and in previous reports (11,(16)(17)(18)(19)(20)(21). Administration routes and drug doses were selected based on previous studies that showed a significant renal protective effect in a Tac-induced mouse model of renal injury (11).…”
Section: Tac-induced Renal Injury Mouse Modelmentioning
confidence: 99%
“…48 In addition to AD, the most common neurodegenerative disease, Parkinson's disease (PD), the second most common neurodegenerative disease, 49 has also been tied to Klotho pathways. [50][51][52] Beyond AD and PD, age-related declines in Klotho 8,13,17,24,53 are associated with a range of other deteriorating central nervous system (CNS) processes. 17,24 For example, mounting evidence implicates dysregulation of Klotho in shared mechanistic pathological relationships linking iron and myelin in various common and rare brain diseases, [54][55][56] including abnormalities in myelination and the maturation of oligodendrocytes that are central to the pathogenicity of diseases such as multiple sclerosis (MS) 26,56,57 and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%